World experience in transport safety: low cost and quikly implemented measures - A. I. Panshin (Путеводитель предпринимателя, 2021)
The article analyzes the world experience in the field of security. The existing experience, the possibility of its use in modern conditions in Russia is analyzed. Analysis of foreign experience has shown that the current state of transport security requires serious study and clearer measures, but they are not possible without improving legal regulation and without introducing modern technologies.